MiR‐150‐504‐519d inhibits the growth of human colorectal cancer cell line SW48 and downregulates c‐FLIP receptor. Issue 5 (12th December 2018) - Rong, Guoqiang; Yang, Xiaodong; Wu, Haorong; Wu, Yongyou
Abstract: microRNAs (miRNAs) are noncoding RNAs that regulates the expression of target messenger RNAs (mRNAs). c‐FLIP is an inhibitor of cell apoptosis through inhibition of caspase 8. miR‐150, miR‐504, and miR‐519d were related to cancer cell proliferation, invasion, and migration in colorectal cancer (CRC). However, the role of miR‐150‐504‐519d in CRC has not been studied and the relationship between miR‐150‐504‐519d and c‐FLIP remains unclear. In this study, we found that c‐FLIP was upregulated in CRC tissues, without detectable expression in normal CRC tissues. Using SW48 cell line, we further showed that miR‐150‐504‐519d inhibited migration, invasion, and promoted apoptosis of SW48 cells. Moreover, in SW48 cell line transfected with miR‐150‐504‐519d, the protein expression of c‐FLIP was significantly lower compared with cells transfected with scramble. Our results demonstrated upregulation of c‐FLIP in CRC, which was downregulated in SW48 cells after the transfection of miR‐150‐504‐519d, suggesting that manipulation of miR‐150‐504‐519d expression might be a novel approach for the treatment of colorectal cancer. Abstract : In this study, miR‐150‐504‐519d can target c‐FLIP and inhibit the growth activity of colorectal cancer cells in vitro. The downregulation of c‐FLIP by miR‐150‐504‐519d may demonstrate why the overexpression of miR‐150‐504‐519d can restrain colorectal cancer cell growth and proliferation.